Role of Preclinical Arthritis Models for the Clinical Translation of Anti-Arthritic Therapeutics - L Ronibala Singha; Malay K Das (Tabriz University of Medical Sciences, 2023)
The overcomplicated and elusive pathophysiology with unclear etiology, have been the main driving force of the medical scientists all over the world to develop a predictive, reliable, robust and reproducible simulation model of arthritis. This review highlights osteoarthritis and rheumatoid arthritis with distinct conditions pertaining to each type of disease. The advances in various in vitro and in vivo experimental models of osteoarthritis and rheumatoid arthritis have been presented along with their pros and cons for antiarthritic drug discovery and formulation development. Additionally, the ethical issues to be considered while selecting animal models and handling them have been covered briefly. The current status quo on clinical trials of antiarthritic therapeutic interventions has also been covered.